PERENCANAAN AGROWISATA MINA PADI DI DELI SERDANG DENGAN PENDEKATAN ARSITEKTUR BIOKLIMATIK - Valentine, Jesslyn; Ritonga, Isniar TL; Endi Martha Mulia (Jurnal Sains dan Teknologi ISTP, 2024)
Agriculture and fisheries owned in Deli Serdang are potential natural resources which must also be preserved and developed. So the selection of the Mina Padi Agrotourism design is a solution that can increase this potential. Simultaneous use of land for planting rice and raising fish for educational and recreational functions. Deli Serdang in 2023 is now a strategic area. Starting from adequate land to achievements that are easy to reach. Deli Serdang is even though in terms of transportation it is very easy to access. Starting from the residents of downtown Medan which can indeed be reached via the Kuala Namu Airport toll road and the Lubuk Pakam City Toll Road. Not only that, the two different sides of Lubuk Pakam and Kuala Namu Airport can also be accessed from Medan city center by train. Even from the air, namely airplanes, which have the potential for residents outside the island to also visit Deli Serdang. This agrotourism can of course be well known and developed by implementing bioclimatic architecture that takes into account the surrounding environment to provide long-term impacts for buildings in planning. So this can be a good complex idea.